2012
DOI: 10.5098/fhp.v3.1.3001
|View full text |Cite
|
Sign up to set email alerts
|

Flat Plate Heat Pipes: From Observations to the Modeling of the Capillary Structure

Abstract: This paper presents a synthesis of observations made inside six different flat plate heat pipes (FPHPs). Silicon and copper systems with different capillary structures and sizes are studied. They are hermetically sealed on their upper face with a transparent plate, which enables liquid-vapor interface observations. A confocal microscope is used to measure the liquid film shapes inside the systems and describe the meniscus curvature radius from the evaporator to the condenser. Physical mechanisms, including the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Under the same conditions, there is a reduction in the radius of curvature of the liquid meniscus in the condenser. This has been experimentally found by F. Lefèvre et al [ 18 ], who showed that if the space through which the vapor flow decreases by 1 mm, the heat transfer capacity of the FMHP decreases by up to 35%. An important condition in the design of an FMHP is the capillary boundary.…”
Section: Introductionsupporting
confidence: 61%
“…Under the same conditions, there is a reduction in the radius of curvature of the liquid meniscus in the condenser. This has been experimentally found by F. Lefèvre et al [ 18 ], who showed that if the space through which the vapor flow decreases by 1 mm, the heat transfer capacity of the FMHP decreases by up to 35%. An important condition in the design of an FMHP is the capillary boundary.…”
Section: Introductionsupporting
confidence: 61%
“…Estimations of the capillary structure properties have already been presented in previous works using the model of Lefèvre and Lallemand [20] in the case of configuration B. This approach was efficient to estimate the properties of longitudinal grooves [27], crossed grooves [26] and metallic meshes [28]. The present analytical model enables the generalization of this approach for other heat pipe configurations.…”
Section: Estimation Of the Properties Of The Capillary Structure By Cmentioning
confidence: 91%
“…Nucleation is typically considered a cause of dry-out in a variety of wicks and referred to as the boiling limit [18]. However, several studies have shown that nucleation in grooved wicks does not constitute an operation limit and may even increase the performance of the heat pipe [19,20]. Chen et al [21] studied capillary and boiling limits in 200-500 µm square cooper grooves.…”
Section: Preliminary Tests and Repeatabilitymentioning
confidence: 99%